Changing water use and adaptive strategies along rainfall gradients in Mediterranean lupins. (2nd January 2020) - Berger, J. D.; Ludwig, C.; Whisson, K.
Abstract: There is growing interest in harnessing the genetic and adaptive diversity of crop wild relatives to improve drought resilience of elite cultivars. Rainfall gradients exert strong selection pressure on both natural and agricultural ecosystems. Understanding plant responses to these facilitates crop improvement. Wild and domesticated narrow‐leafed lupin (NLL) collected along Mediterranean terminal drought stress gradients was evaluated under contrasting reproductive phase water supply in controlled field, glasshouse and cabinet studies. Plant phenology, growth and productivity, water use and stress responses were measured over time. There is an integrated suite of adaptive changes along rainfall gradients in NLL. Low rainfall ecotypes flower earlier, accumulate lower seed numbers, biomass and leaf area, and have larger root:shoot ratios than high rainfall ecotypes. Water‐use is lower and stress onset slower in low compared to high rainfall ecotypes. Water‐use rates and ecotypic differences in stress response (Ψleaf decline, leaf loss) are lower in NLL than yellow lupin (YL). To mitigate the effects of profligate water use, high rainfall YL ecotypes maintain higher leaf water content over declining leaf water potential than low rainfall ecotypes. There is no evidence for such specific adaptation in NLL. The data suggests that appropriate phenology is the key adaptive trait to rainfall gradients in NLL because of the flow‐on effects on biomass production, fitness, transpiration and stress onset, and the lack of physiological adaptations as in YL. Accordingly, it is essential to match phenology with target environment in order to minimize risk and maximize yield potential. Abstract : There is an integrated suite of adaptive changes along rainfall gradients in narrow‐leafed lupin which we can exploit by matching phenology very closely with target climates.